IMPROVING THE COMPETENCY OF BIOLOGY TEACHERS OF SENIOR HIGH SCHOOL/VOCATIONAL HIGH SCHOOL IN BENER MERIAH DISTRICT THROUGH TRAINING ON THE DEVELOPMENT OF INDEPENDENT CURRICULUM TEACHING MODULES - Puspa, Vivera Ruselli; Hafnati Rahmatan; Nir Fathiya (Jurnal Pengabdian Bangsa, 2024)
Bener Meriah Regency is one of the regencies in Aceh Province where several schools have implemented the Independent Curriculum. The results of interviews conducted with the Chairperson of the Subject Teachers' Deliberation (MGMP) for Biology in Bener Meriah Regency showed that high school/vocational high school biology teachers did not yet fully understand the development of the Independent Curriculum teaching module. This activity aims to improve teacher competence related to the development of the Independent Curriculum teaching module so that teachers have the knowledge to develop modules for the implementation of the Independent Curriculum in their schools. The data for this study used a questionnaire with an instrument consisting of 5 statements regarding the development of the Independent Curriculum teaching module for high school/vocational high school biology teachers in Bener Meriah Regency. The data is presented descriptively. The results of the activity show that high school/vocational high school biology teachers in Bener Meriah Regency agree with the development of the Independent Curriculum teaching module. This is indicated by the percentage of questionnaire results obtained, namely 93% of biology teachers chose to agree with the freedom of an educator in choosing and modifying teaching tools and 100% of biology teachers chose to agree with the objectives of the teaching module, the needs of students, the criteria for teaching modules, and the objectives of developing teaching modules. The enthusiasm of the participants, the survey results, and the modules produced by the teachers prove the success of this activity.